Analisis Pengaruh Asset Structure, Earning Volatility, dan Return on Asset terhadap Capital Structure pada Perusahaan Sektor Energi di Bursa Efek Indonesia - Lorensia Nevi Widayati; Katarina Agnes (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
The purpose of this study is to analyze how asset structure, earning volatility, and return on asset affect the capital structure of energy companies listed on the Indonesia Stock Exchange. This study uses a quantitative method with an associative approach as a supporting factor. The research population consists of 91 companies in the energy industry, with a sample of 15 companies selected through purposive sampling for the observation period of 2020-2024. Data collection was carried out through documentary studies, sourced from the companies’ annual financial reports. The analysis methods used include descriptive statistical analysis, classical assumption tests, and multiple linier regression. The analysis process was carried out using SPSS version 26 software. The main findings of this study indicate that asset structure has a significant positive effect on capital structure, while earning volatility and return on asset have a significant negative effect on capital structure. With an influence level of 87,1%, these three independent indicators contribute significantly to capital structure. These findings help management understand the internal elements of a company that can influence financial decisions.